2022
DOI: 10.1002/er.7632
|View full text |Cite
|
Sign up to set email alerts
|

Role of triethanolamine in forming Cu 2 ZnSnS 4 nanoparticles during solvothermal processing for solar cell applications

Abstract: Summary Herein, Cu2ZnSnS4 (CZTS) nanoparticles were synthesized utilizing different amounts of triethanolamine (TEA) (2, 3, 4, and 5 mg/mL) via a simple solvothermal method. The TEA concentration's influence on the structure, phase formation, morphology, and composition of the CZTS nanoparticles was studied using various experimental techniques. XRD and Raman spectroscopy analyses indicated that the obtained product consisted of single‐phase CZTS nanoparticles with a kesterite structure and average crystal siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…Several research groups have reported results for CZTS-based solar cells fabricated by the solvothermal method [ 75 , 76 , 77 , 78 ]. To obtain CZTS absorber layers, firstly the solvothermally synthesized CZTS nanoparticles are dispersed in solvents to create a paste or ink.…”
Section: Processing Technologies For Thin Kesterite Czts Absorber Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several research groups have reported results for CZTS-based solar cells fabricated by the solvothermal method [ 75 , 76 , 77 , 78 ]. To obtain CZTS absorber layers, firstly the solvothermally synthesized CZTS nanoparticles are dispersed in solvents to create a paste or ink.…”
Section: Processing Technologies For Thin Kesterite Czts Absorber Filmsmentioning
confidence: 99%
“…The fabricated glass/FTO/CZTS/CdS/i-ZnO/AleZnO/Ag solar cells were characterized by an optical bandgap of 1.52 eV and a poor power conversion efficiency of only 0.16%. Using the solvothermal method, Al-Hadeethi et al studied the impact of the concentration of triethanolamine (TEA) on the structure, phase formation, morphology, and composition of the resulting CZTS nanoparticles [ 78 ]. The authors fabricated a SLG/Mo/CZTS/CdS/i-ZnO/Al:ZnO/Al structure using CZTS particles synthesized with a TEA concentration of 5 mg/mL, and the best demonstrated solar conversion efficiency was reported to be 4.33%.…”
Section: Processing Technologies For Thin Kesterite Czts Absorber Filmsmentioning
confidence: 99%